Perancangan Model Simulasi Tata Letak Gudang Bahan Baku Menggunakan Metode Shared Storage Pada PT. Hyundai Indonesia Motor - Parwadi Moengin; Ilyas Noor Firdaus; Sucipto Adisuwiryo (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2018)
Problems at PT. Hyundai Indonesia Motor occurs in the warehouse of raw materials for local parts, Thailand parts, andbulky & trim areas where laying raw materials is not regular, does not fit shelves or pallets and there is no layout for laying rawmaterials on the shelves, so operators have difficulty finding raw materials to be processed and cause the time to extract raw materialsis greater and there is a delay in the delivery of raw materials to the production line. The purpose of this study was to design a simulationmodel for improving the warehouse layout of raw materials to minimize the time taken to take raw materials to the production line.The first step in evaluating the raw material warehouse layout at PT. Hyundai Indonesia Motor is by using a checksheet and a map ofthe process of extracting raw materials used to determine the condition of the warehouse of raw materials and the process of extractingraw materials. Next, make improvements to the raw material warehouse layout using the shared storage method. The first threeproposals proposed using the initial layout with the addition of material handling in the local area, the second proposal using the sharedstorage method, the third proposal using the shared storage method with the addition of material handling in the local area, thenselecting the proposal using the benferroni method and using the check sheet evaluation results so that the best proposal is obtained,namely in the third proposal with the fastest simulation time, namely the average simulation time of 63.47 hours. Compared with theinitial simulation which has a simulation time of 125.14 hours, in the third proposal there is a minimum time so that the time differenceis 61.7 hours for the initial simulation.